STUDY OF THE INCIDENCE AND RISK FACTORS OF ULCERATIVE COLITIS IN WOMEN IN ANDIJAN - A'zamov Saidakbar Mukhamadali ugli,; Saliev D.Q, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2026)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease characterized by recurrent inflammation of the colonic mucosa, leading to significant physical, psychological, and social burdens. In recent decades, the incidence of UC has been increasing worldwide, particularly among women, which has raised concerns regarding gender-specific risk factors and regional determinants of the disease.